Assessment of general health and quality of life in patients with acne using avalidated generic questionnaire - Al Ronaee, A. A. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
OBJECTIVES: The study was designed to utilize the SF-36, a validated generic questionnaire, to assess acne patients' view of their general health and quality of life. METHODS: The subjects were 454 acne patients (237 males, 217females) visiting an outpatient clinic at Qassim University. An Arabic translation of the SF-36 questionnaire, culturally adapted and validated, wasused to assess eight life-quality dimensions. Data regarding demographics, disease grade, duration, and treatment were also included in the questionnaire. The internal consistency reliability of the multi-item scales was assessed using Cronbach's coefficient alpha. Descriptive statistics were conducted with independent and paired-sample t-tests as well as one-way ANOVA for metric variables; and Xi(2) and Fisher's exact tests were used for categorical variables. Spearman's rank correlation was used for associations.All tests were two-sided, and the level of significance was set at phi < 0.05. RESULTS: The scores for physical functioning, role physical, role emotional, and vitality dimensions were below 60%. About 81.5% of respondents rated their health as either "fair" or "poor", and only 25% said their general health was better than the previous year. Females were more likely to report better general health than males (phi = 0.001). Education level negatively correlated with mental health, role emotional, social functioning, general health, and bodily pain. Rural patients showed better general health (phi = 0.003). Married persons rated their general health better than single patients (phi = 0.002). Mild and shorter-duration acne wasassociated with a better general health score compared to the previous year(phi = 0.01 and 0.001, respectively). (Abstract truncated at 2000 characters)
Keywords: Acne Vulgaris; Adult; Akna navadna; akne; ankete; Health Status; Health Status Indicators; Kvaliteta življenja; Odrasli; Quality Of Life; Questionnaires; Social Support; Socialna pomoč; Socioeconomic Factors; Socioekonomski faktorji; Zdravstveno stanje; Zdravstveno stanje, kazalci